Neuroprotective activity of Ulmus pumila L. in Alzheimer's disease in rats; role of neurotrophic factors. Issue 12 (December 2020) - Hussein, Rehab A.; Afifi, Ahmed H.; Soliman, Ahmed A.F.; El Shahid, Zeinab A.; Zoheir, Khairy M.A.; Mahmoud, Khaled M.
Abstract: Alzheimer's disease (AD) is one of the most prevalent neurodegenerative disorders which affects the hippocampus and cortical neurons leading to impairment of cognitive ability. Treatment of AD depends mainly on acetylcholinesterase inhibitors, however, a novel therapeutic approach is introduced based on the maintenance of neuronal viability and functionality exerted through neurotrophic factors. In the current study, Ulmus pumila L. leaves alcoholic extract was investigated for its neuroprotective activity in AlCl3 -induced AD in rats. Rats were orally treated with AlCl3 (17 mg/kg) for 4 weeks followed by U. pumila extract (150 mg/kg b.wt.) for another 6 weeks. Treatment of neuro-intoxicated rats with U. pumila extract resulted in a significant regulation in neurotrophic factors; brain derived neurotrophic factor and transforming growth factor-β and pro-inflammatory cytokine; TNF. It also induced an elevation in serum levels of monoamine neurotransmitters; norepinephrine, dopamine and serotonin and a decline in brain acetlycholinesterase activity. U. pumila extract also showed potent antioxidant activity as indicated by the declined malondialdehyde and elevated reduced glutathione, catalase and super oxide dismutase levels in AD rats' brains. Histological improvement was detected in the cerebral cortex, the hippocampus and striatum of the treated rats . The phytochemical analysis of U. pumila extract revealed high contents of flavonoids and phenolics and the major compounds were isolated and chemically characterized. Additionally, U. pumila extract and the isolated compounds exerted a prominent activity in in-vitro acetylcholinesterase inhibition assay with kaempferol-3-O-β-glucoside being the most potent compound showing IC50 of 29.03 ± 0.0155 μM. A molecular docking study indicated high affinity of kaempferol-3-O-β-robinobioside on acetylcholine esterase binding site with estimated binding free energy of –8.26 kcal/mol. Abstract : Ulmus pumila L. ; Neuroprotective activity; Alzheimer's disease; Acetylcholinesterase inhibitors; BDNF; TGF-β1; Natural product chemistry; Public health; Neurology; Pharmacology; Alternative medicine